A Critical Thinking Profile of Mathematics Education Students in Solving Ill-Structured Problem based on Mathematical Ability - Jaelani, Abd Kadir; Hasbi, Muhammad; Baharullah, Baharullah (Universitas Muhammadiyah Mataram, 2023)
This study aims to describe the critical thinking profile of mathematics education students in solving ill-structured problems based on mathematical ability. The critical thinking profile in solving the described ill-structured problem consists of several stages, namely (1) Analyze; (2) Browse; (3) Create; (4) Decision-making; (5) Evaluate; and (6) List or with the term A-B-C-D-E plus L based on critical thinking skills, namely (1) Interpretation; (2) Analysis; (3) Conclusion; (4) Evaluation; (5) Explanation; and (6) Self-regulation. The subjects of this study consisted of one student of mathematics education who had the high mathematical ability and one student of mathematics education who had the moderate mathematical ability. They were interviewed based on the results of the Ill-Structured problem-solving. This research used a descriptive qualitative approach. The data obtained were validated, then analyzed with several steps, namely: reduction, data presentation, categorization, interpretation, and inference. The results showed that the mathematics education students carried out critical thinking processes in solving ill-structured problems through six (6) stages, namely: Analyze, Browse, Create, Decision-making, Evaluate, and List or with the term A-B-C-D-E plus L, those which refer to the stages of critical thinking skills, including Interpretation, Analysis, Conclusions, Evaluation, Explanation, and Self-regulation.